Public libraries as partners in youth development establishing youth programs and services in the Quezon City Public Libraries - Panti, Michelle F. (2004)
The purpose of the study was to determine the reading habits and leisure activities of the third and fourth year high schools students in Quezon City as well as their source of reading materials, their awareness of the existence of public libraries in Quezon City and find out who encourage and inspire them to visit the public libraries in Quezon City and to recommend after-school programs through youth programs and services in Quezon City public libraries. The descriptive survey method was used with the questionnaire as well as observation and interviews. The data gathered were tallied, tabulated and interpreted using frequencies and percentages.